2021
DOI: 10.1159/000511405
|View full text |Cite
|
Sign up to set email alerts
|

Association of Race with In-Hospital and Post-Hospitalization Mortality in Patients with Acute Kidney Injury

Abstract: Introduction: Acute kidney injury (AKI) is known to be associated with increased mortality, and racial differences in hospital mortality exist in patients with AKI. However, it remains to be seen whether racial differences exist in post-hospitalization mortality among AKI patients. Methods: We analyzed data of adult AKI patients admitted to the University of Virginia Medical Center between January 1, 2001, and December 31, 2015, to compare in-hospital and post-hospitalization mortality among hospitalized black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…In our study that included data of 11,567 AKI patients managed at the University of Virginia Health System, we demonstrated that Black patients had lower in-hospital mortality than Whites, with adjusted odds ratio 0.82, 95% confidence interval 0.70–0.96, p = 0.0015. Following further analysis, we also extended the findings of the previous workers by demonstrating Black patients had lower 90-day post-hospitalization mortality and better long-term survival advantage when compared to their White counterparts [ 15 ]. Similarly, data from the United States Renal Data System (2021 USRDS Annual Data Report) also showed a survival advantage for Black populations compared to White populations after 24 months’ follow-up; Black patients had 38,6% death rates compared to 41.7% death rates in White patients.…”
Section: Racial Disparities In the Aki-related Mortalitysupporting
confidence: 72%
See 3 more Smart Citations
“…In our study that included data of 11,567 AKI patients managed at the University of Virginia Health System, we demonstrated that Black patients had lower in-hospital mortality than Whites, with adjusted odds ratio 0.82, 95% confidence interval 0.70–0.96, p = 0.0015. Following further analysis, we also extended the findings of the previous workers by demonstrating Black patients had lower 90-day post-hospitalization mortality and better long-term survival advantage when compared to their White counterparts [ 15 ]. Similarly, data from the United States Renal Data System (2021 USRDS Annual Data Report) also showed a survival advantage for Black populations compared to White populations after 24 months’ follow-up; Black patients had 38,6% death rates compared to 41.7% death rates in White patients.…”
Section: Racial Disparities In the Aki-related Mortalitysupporting
confidence: 72%
“…Even though African Americans (Blacks) in the general population are at a higher risk of cardiovascular and non-cardiovascular mortality when compared to Whites [ 67 , 68 ], several reports have suggested that a paradox exists for individuals with AKI, with Black patients having better survival rates than their White counterparts [ 15 , 26 , 69 ]. Waikar et al [ 26 ], in their study of hospitalized acute renal failure patients between 2000 and 2003 using the Nationwide Inpatient Sample, showed a survival advantage among Black patients with AKI compared to their White counterparts, with Black patients having 16% (95% confidence interval, 10–20%) lower odds for death than White patients with AKI.…”
Section: Racial Disparities In the Aki-related Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Reports from other areas have shown that black patients tend to have a higher risk of AKI than white patients, and Asians also have a relatively low incidence of AKI ( Hassan and Balogun, 2022 ). However, black patients with AKI would have a lower in-hospital mortality rate ( Hassan et al., 2021 ). The association between race and AKI in PJI remains unknown, but warrants further investigation to improve prognosis.…”
Section: Discussionmentioning
confidence: 99%